Turning Pirates into Subscribers: A Status Quo Bias Perspective on Online Movie Service Switching Intention - Panca O. Hadi Putra; Muhammad Imam Santosa; Ika Chandra Hapsari; Achmad Nizar Hidayanto; Sherah Kurnia (Emerging Science Journal, 2022)
This study aims to analyze the factors that influence a person's intention to use a subscription-based streaming service application using the perspective of the inertia of piracy movie application users. This study investigates the factors that affect the inertia of movie piracy application users. The theory used is a combination of the status quo bias theory and coping theory. This research uses a quantitative approach and an online survey method for data collection. Data collection resulted in 378 responses that were subsequently analyzed using the covariance-based structural equation modeling (CB-SEM) technique. It was found that inertia (the level of user inertia) negatively affects intention to use (the intention to use a subscription-based streaming service application) and convenience. In addition, convenience, perceived controllability (a person's level of control over the application), and morality positively influence intention to use. Furthermore, it was also found that perceived cost and personalization do not affect the intention to use. Inertia is also positively and significantly influenced by the transition cost (effort to move). The factors that have the highest correlation values are transition cost and inertia. Doi: 10.28991/ESJ-2022-06-05-06 Full Text: PDF